Preventing, Reducing and Ending LGBTQ2S Youth Homelessness: The Need for Targeted Strategies - Abramovich, Alex (2016)
Gender non-conforming and sexual minority youth are overrepresented in the homeless youth population and are frequently discriminated against in shelters and youth serving organizations. This paper provides a contextual understanding of the ways that institutional and governmental policies and standards often perpetuate the social exclusion of lesbian, gay, bisexual, transgender, queer, and 2-Spirit (LGBTQ2S) youth, by further oppression and marginalization. Factors, including institutional erasure, homophobic and transphobic violence, and discrimination that is rarely dealt with, addressed, or even noticed by shelter workers, make it especially difficult for LGBTQ2S youth experiencing homelessness to access support services, resulting in a situation where they feel safer on the streets than in shelters and housing programs. This paper draws on data from a qualitative Critical Action Research study that investigated the experiences of a group of LGBTQ2S homeless youth and the perspectives of staff in shelters through one-on-one interviews in Toronto, Canada. One of the main recommendations of the study included the need for governmental policy to address LGBTQ2S youth homelessness. A case study is shared to illustrate how the Government of Alberta has put this recommendation into practice by prioritizing LGBTQ2S youth homelessness in their provincial plan to end youth homelessness. The case study draws on informal and formal data, including group activities, questions, and surveys that were collected during a symposium on LGBTQ2S youth homelessness. This paper provides an overview of a current political, social justice, and public health concern, and contributes knowledge to an under researched field of study by highlighting concrete ways to prevent, reduce, and end LGBTQ2S youth homelessness.